Understanding health professionals intention to use telehealth in Yemen: Using the delone and McLean IS success model - Al-Fadhli A.A.; Othman M.; Ali N.; Al-Jamrh B.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Medical computing; Rural areas; Health professionals; Health-care system; Information quality; Innovative technology; IS success model; Quantitative approach; Unified theory of acceptance and use of technology; User satisfaction; eHealth